(untitled) (Brazilian Journal of Health Research, 2021)
Introduction: Nutritional status and food when inadequate are associated with chronic non-communicable diseases (NCDs) in adults. Thus, it is necessary to monitor the nutritional aspects of this population for local procedures and to prevent NCDs. Objective: To evaluate the food consumption and nutritional status of adults registered in the Food and Nutrition Surveillance System (SISVAN) in Piauí, Brazil. Methods: Cross-sectional study, prepared with data from SISVAN. The sample consisted of adults aged 20 to 59 years old, registered in the Piauí system in 2018. SISVAN generates data on food consumption and nutritional diagnosis in absolute numbers and percentages, which were used to formulate as tables (analysis descriptive). Results: There was a prevalence of overweight of 38.87% for men and 35.70% for women. When grouping the three types of obesity, 20.91% and 21.07% were obtained in males and females, respectively. Regarding food consumption, only 12% of individuals consumed at least 3 meals / day and 42% until them watching television. It was also found that 91% of adults until beans the day before. As for ultra-processed foods, the group of stuffed biscuits, sausages and instant noodles consumed 25%, 21% and 30% of the sample, respectively. Conclusion: There was a high percentage of overweight. In the diet, there was a high frequency of consumption of beans and ultra-processed foods. A small portion consumed at least three meals / day. Thus, it highlights the importance of strategic public health actions to combat excess weight and improve the dietary aspects of adults from Piauí.